The Factors Influencing Intention to Study Via Online Education: The Case Study of People In Bangkok, Thailand - Dinesh Elango; Rawin Vongurai; Kirana Srifah (Society of Visual Informatics, 2018)
Recently, online education or online learning is an interest in Thailand and some of Thai people study via the internet, noticed that in Thailand not only some universities provide online education such as Massive Open Online Courses, called MOOCs, but various schools and institutions provide online learning for their students as well.Online education provides an opportunity to improve people at the lower cost via computer technology, which is beneficial to developing countries.Thailand is still a developing country and online education is likely to be a new trend in Thailand because it reduces costs and enhances the quality of education.Consequently, this research analyzes influencing factors which have an impact on usage intention of online education. This research aims to study various factors, which are able to be improved for usage intention of online education in Bangkok, Thailand, in the future. Based on the conceptual framework in this research, it consists of social influence, information quality, system quality, function quality as key factors of usage intention.The research applied many methods such as Single Linear Regression and Multiple Linear Regression to analyze all hypotheses with 441 respondents who live in Bangkok, Thailand,and use online education.This paper addresses the effects of information quality, system quality, function quality, and social quality influencing toward usage intention of online education. Besides, social quality not only affects usage intention but also has an impact on other factors which information quality, system quality, and function quality.